Learning and Adaptation in Polycentric Transport Governance: The Case of the Dutch Brabant Accessibility Agenda. Issue 7 (August 2022) - Bousema, Ingo; Busscher, Tim; Rauws, Ward; Leendertse, Wim
The future of urban-regional transport crucially depends on the ability of transport governance systems to adapt. Polycentric theory claims that the presence of polycentric attributes and conditions enables governance systems to learn and adapt. However, an analysis of the Dutch Brabant Accessibility Agenda shows that their presence says little about the adaptive capacity of transport governance systems because learning and adaptation are influenced by dependencies. To optimize the adaptive capacity of transport governance systems, it is therefore vital to acknowledge both the diverse ways in how they learn and adapt, and the dependencies that shape these processes.